Priapismo: abordaje clínico y manejo de urgencia - Córdova P, Leopoldo (Revista Hospital Clínico Universidad de Chile, 2021)
Priapism is a persistent erection, often painful, lasting more than 4 hours and unrelated to sexual stimulation. Based on clinical and pathophysiological features, priapism can be classified as ischemic, nonischemic and stuttering. Ischemic priapism is the most frequent form and represents a urological emergency. Although it is described as a low frequency entity, its timelydiagnosis and immediate intervention are essential in the reestablishment of cavernous blood flow and in the prevention of necrosis and permanent erectile dysfunction. Intracavernous blood aspiration and injection of a-adrenergic agents correspond to the first-line options for the management of cases of ischemic priapism. Surgical shunts continue to be the most widely used surgical option for the management of prolonged ischemic priapism refractory to non-invasive management, with emerging evidence supporting the early implantation of a penile prosthesis. The objective of this review article is to describe the keys to the clinical approach and acute management of priapism in the emergency department.